Frequency-modulated atomic force microscopy localises viscoelastic remodelling in the ageing sheep aorta. (December 2016) - Akhtar, R.; Graham, H.K.; Derby, B.; Sherratt, M.J; Trafford, A.W.; Chadwick, R.S.; Gavara, N.
Abstract: Age-related aortic stiffening is associated with cardiovascular diseases such as heart failure. The mechanical functions of the main structural components of the aorta, such as collagen and elastin, are determined in part by their organisation at the micrometer length scale. With age and disease both components undergo aberrant remodelling, hence, there is a need for accurate characterisation of the biomechanical properties at this length scale. In this study we used a frequency-modulated atomic force microscopy (FM-AFM) technique on a model of ageing in female sheep aorta (young: 18 months, old: >8 years) to measure the micromechanical properties of the medial layer of the ascending aorta. The novelty of our FM-AFM method, operated at 30 kHz, is that it is non-contact and can be performed on a conventional AFM using the ׳cantilever tune' mode, with a spatial (areal) resolution of around 1.6 μm 2 . We found significant changes in the elastic and viscoelastic properties within the medial lamellar unit (elastic lamellae and adjacent inter-lamellar space) with age. In particular, there was an increase in elastic modulus (Young; geometric mean (geometric SD)=42.9 (2.26) kPa, Old=113.9 (2.57) kPa, P <0.0001), G ′ and G ″ (storage and loss modulus respectively) (Young; G ′=14.3 (2.26) kPa, Old G ′=38.0 (2.57) kPa, P <0.0001; Young; G ″=14.5 (2.56) kPa, Old G ″=32.8 (2.52) kPa, P <0.0001). The trends observed in the elastic properties with FM-AFM matched those we have previously found using scanning acoustic microscopy (SAM). The utility of the FM-AFM method is that it does not require custom AFM hardware and can be used to simultaneously determine the elastic and viscoelastic behaviour of a biological sample. Graphical abstract: